UJI EFEK ANTIPIRETIK EKSTRAK ETANOL BIJI KORO BENGUK (Mucuna pruriens L.) DENGAN METODE SOKHLETASI PADA TIKUS PUTIH JANTAN GALUR WISTAR (Rattus norvegicus L.) - Putri, Alifa Ayuanti Santosa; Kusuma, Eka Wisnu (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2024)
Mucuna pruriens L is a plant that lives in a tropical climate and is widely found in Indonesia. Public knowledge on how to use velvet bean is still limited. Mucuna pruriens L plants have benefits such as antibacterial, gout, cancer, diabetes, kidney stones. The purpose of this study was to determine the effectiveness and antipyretic effect of Mucuna pruriens L ethanol extract. This study used the socleation method as an extraction method. Velvet Mucuna pruriens L ethanol extract was given orally to male white rats. The administration of extracts was divided into 5 groups, namely group 1 given CMC-Na as a negative control, group II paracetamol 45 mg / kg BB, group III 200 mg / KgBB and group IV 300 mg / KgBB and group V 400 mg / KgBB. The body temperature of the rats was measured at intervals of 30 minutes to 150 minutes when they were given the test substance orally. Based on research analysis showed that at a dose of 400 mg / KgBB mhad a comparable entipyretic effect strength in positive controls. Therefore, Mucuna pruriens L have potential as antipyretic drugs.